Discovering interrelated natural mutations of efflux pump KmrA from Klebsiella pneumoniae that confer increased multidrug resistance. (9th May 2022) - Li, Ying; Ge, Xizhen
Abstract: Klebsiella pneumoniae is a notorious pathogen that can cause multiorgan infections, which is difficult to treat mainly due to the widely distributed efflux pumps. Our previous research discovered the upregulation of efflux pump KmrA conferred enhanced antibiotic resistance, while the export mechanism and its natural mutations across K . pneumoniae isolates remain unclear. Herein, we analyzed the natural mutations of KmrA across 830 K . pneumoniae genomes to discover interrelated amino‐acid substitutions (simultaneously occurred substitutions) that increase drug export. We identified two variants that contain triple amino‐acid substitutions near the periplasmic side and then confirmed their roles in enhancing multidrug resistance of recombinant K . pneumoniae strains. Molecular dynamics simulations were conducted to illustrate the reason for their promoted export efficiencies. Our data indicated the triple substitutions resulted in KmrA's both stronger hydrophilic interaction with water and hydrophobic interaction with membrane. Moreover, these substitutions promoted the flexibilities of KmrA that could facilitate the conformational switch. In parallel, stronger ionic interactions (salt bridges) at cytoplasmic side also suggested the higher possibilities for the reciprocal movements. Collectively we demonstrated the potential risk of the interrelated natural mutations in efflux pump to antibiotic resistance of K . pneumoniae and provided insights into the mechanism of the enhanced drug export.